2015
DOI: 10.1001/jamaoto.2015.1756
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Objective Compliance During Oral Appliance Therapy in Patients With Sleep-Related Disordered Breathing

Abstract: clinicaltrials.gov Identifiers: NCT01284881 and NCT01532050.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…With the advent of objective monitoring, in two prospective small-scale studies, a median use of MAD therapy for 6.4 h/night was reported after 3 months and a mean use of 6.1 h/night after 1 year. 52,53 Approximately 29% to 83% of patients using CPAP are noncompliant.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of objective monitoring, in two prospective small-scale studies, a median use of MAD therapy for 6.4 h/night was reported after 3 months and a mean use of 6.1 h/night after 1 year. 52,53 Approximately 29% to 83% of patients using CPAP are noncompliant.…”
Section: Discussionmentioning
confidence: 99%
“…4 Objective measurements of OA usage after 3 months of OA treatment ranged from a mean of 6.4 hours to 6.6 hours per night. 35,36 A meta-analysis of 6 studies encompassing both subjective and objective MAD compliance measures reported an additional 1.1 hours per night use of MAD over CPAP. 33 A majority of crossover trials report that MADs are preferred to CPAP, which may imply better patient compliance with MADs.…”
Section: Oxygenationmentioning
confidence: 99%
“…46,48 ORAL APPLIANCE ADVERSE EFFECTS Similar to efficacy, adverse side effects have a dose-dependent relationship with protrusion. 29 A balance must be struck between efficacy and side effects because more adverse effects reduce long-term compliance, 35,49 resulting in patients terminating MAD therapy. 50,51 Most adverse effects caused by MADs are mild and transient, occur during the initial phase of therapy, and tend to resolve with time.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
See 2 more Smart Citations